Loneliness and Health Indicators in Middle-Aged and Older Females and Males - Crespo-Sanmiguel, Isabel; Zapater-Fajarí, Mariola; Garrido-Chaves, Ruth; Hidalgo, Vanesa; Salvador, Alicia (Frontiers in Behavioral Neuroscience, 2022)
Loneliness is a complex and uncomfortable feeling that results from the perception of a lack of desired personal and social ties. Loneliness is accentuated with aging. It has been related to a wide range of objective and subjective health indicators and is a risk factor for morbidity and mortality. One of the proposed underlying mechanisms through which loneliness affects health is the dysregulation of the Hypothalamic-Pituitary-Adrenal (HPA) axis. However, the relationship between loneliness and cortisol, the main product of the HPA axis, is unclear and requires more research. The aims of this cross-sectional study were to investigate the relationships between loneliness, subjective health, and cortisol indexes, taking the sex into account, and investigate whether the HPA axis mediates the relationship between loneliness and subjective health. For this purpose, 79 participants (between 55-75 years old) completed several scales on loneliness, depression, perceived stress, psychological and physical health, and social relationships. Various salivary cortisol measurements were obtained on two consecutive days. The initial results showed that loneliness was related to psychological and physical health in the mixed-sex sample. However, when covariates were introduced, loneliness was only associated with psychological health in males. In addition, the cortisol indexes employed were not related to loneliness and did not mediate the relationship between loneliness and subjective health. Hence, we did not find a relevant role of the HPA axis in the association between loneliness and subjective health. More severe perceptions of loneliness would probably be necessary to detect this role. Overall, these results also show that the expected negative outcomes of loneliness associated with aging can be countered by an active life that can compensate for the natural losses experienced with age or at least delay these negative outcomes. Finally, some sex differences were found, in line with other studies, which warrants further examination of social variables and dimensions related to gender in future research.